Karyosystematics and molecular taxonomy of the anomalous blue butterflies (Lepidoptera, Lycaenidae) from the Balkan Peninsula - Vishnevskaya, Maria S. (Comp Cytogenet, 2016)
Abstract. The Balkan Peninsula represents one of the hottest biodiversity spots in Europe. However, the invertebrate fauna of this region is still insufficiently investigated, even in respect of such well-studied organisms as Lepidoptera. Here we use a combination of chromosomal, molecular and morphological markers to rearrange the group of so-called anomalous blue butterflies (also known as ‘brown complex’ of the subgenus Agrodiaetus Hübner, [1822] and as the Polyommatus (Agrodiaetus) admetus (Esper, 1783) species group) and to reveal its cryptic taxonomic structure. We demonstrate that Polyommatus aroaniensis (Brown, 1976) is not as widespread in the Balkans as was previously thought. In fact, it has a dot-like distribution range restricted to the Peloponnese Peninsula in South Greece. Polyommatus orphicus Kolev, 2005 is not as closely related to the Turkish species Polyommatus dantchenkoi (Lukhtanov & Wiemers, 2003) as was supposed earlier. Instead, it is a Balkan endemic represented by two subspecies: Polyommatus orphicus orphicus (Bulgaria) and Polyommatus orphicus eleniae Coutsis & De Prins, 2005 (Northern Greece). Polyommatus ripartii (Freyer, 1830) is represented in the Balkans by an endemic subspecies Polyommatus ripartii pelopi. The traditionally recognized Polyommatus admetus (Esper, 1783) is shown to be a heterogeneous complex and is divided into Polyommatus admetus sensu stricto (the Balkans and west Turkey) and Polyommatus yeranyani (Dantchenko & Lukhtanov, 2005) (east Turkey, Armenia, Azerbaijan and Iran). Polyommatus nephohiptamenos (Brown & Coutsis, 1978) is confirmed to be a species with a dot-like distribution range in Northern Greece. Finally, from Central Greece (Timfristos and Parnassos mountains) we describe Polyommatus timfristos Lukhtanov, Vishnevskaya & Shapoval, sp. n. which differs by its haploid chromosome number (n=38) from the closely related and morphologically similar Polyommatus aroaniensis (n=47-48) and Polyommatus orphicus (n=41-42). We provide chromosomal evidence for three separate south Balkan Pleistocene refugia (Peloponnesse, Central Greece and Northern Greece/South Bulgaria) and stress the biogeographic importance of Central Greece as a place of diversification. Then we argue that the data obtained have direct implications for butterfly karyology, taxonomy, biogeography and conservation.